Penjadwalan Flow Shop Plant P dengan Modified Hodgson Algorithm di PT. X - Adelia Leony Tanuwijaya; Herri Christian Palit (Jurnal Titra, 2021)
PT. X is a glass processing company located in Surabaya. Production system based on a customer order. Production could not work based on the schedule because the software cannot match the knowledge on the production floor. It will cause production cannot follow the schedule and inaccurate estimate completion time. This problem affected the percentage of lateness orders reached 33.07%. This project aims to make a proposed schedule that can minimize tardy jobs. The algorithm used in scheduling is Modified Hodgson Algorithm. This algorithm uses the remaining time of the process to decide the order of the jobs. The results showed that there was no difference between initial and proposed algorithm in almost each case, because the input of the cutting process between the present and proposed algorithm are quit the same. The implementation of proposed scheduling has been done in cutting, edge, drill, and notch process. Problems that often occurred are that the product is still in the previous process. It happened because the scheduling does not consider the transport time. The percentage of conformity between the proposed scheduling with realization for cutting, re-cut, edge square, edge irregular, and drill & notch processes is 100%, 33%, 32%, 35%, and 30%.